Follow-up Study on the Effect of Risk-Stratified, Protocol-Based Perioperative Antibiotic Prophylaxis on Postoperative Infections in a Tertiary Care Neurosurgical Department over 10 Years (2007–2016) - Agarwal, Ashutosh; Borkar, Sachin A.; Kapil, Arti; Dabral, Jyotsna; Suri, Ashish; Kale, Shashank S.; Mahapatra, Ashok K. (Indian Journal of Neurosurgery, 2018)
Objective To study the effectiveness of risk-stratified prophylactic antibiotic policy on meningitis, surgical site, and extraneurosurgical site infections among postoperative neurosurgical patients from the year 2007 to 2016. This is a follow-up study for a similar analysis done from 1994 to 2006, which is published in Neurosurgery.Methods Retrospective audit of 30,251 consecutive neurosurgical cases from January 2007 through December 2016 at a tertiary care center with culture positivity in samples taken from patients showing clinical/radiologic evidence of infection as an objective marker of postoperative infection. Risk-stratified, variable-duration antibiotic prophylaxis policy was followed over 10 years; it was modified in the year 2014, and infections from 2007 to 2013 were compared with 2014 to 2016.Results Over 10 years, there were 2,782 infections in 2,193 (9.45%) patients with meningitis in 281 (0.96%), bloodstream infections in 596 (2.05%), respiratory infections in 913 (3.11%), urinary tract infections (UTIs) in 697 (2.30%), and wound infections in 295 (1.02%) patients. On comparison, the proportion of infections between 2014 and 2016 was significantly lower than that between 2007 and 2013 (4.61 ± 0.14% vs. 11.52 ± 2.2%, p = 0.001). The most common microorganisms were non–lactose-fermenting gram-negative bacilli, followed by Klebsiella and Escherichia coli. The proportion of gram-positive cocci (GPC) was 16.2% with methicillin-resistant Staphylococcus aureus (MRSA) accounting for 5.5% cases.Conclusion A risk-stratified, variable-duration prophylactic antibiotic protocol helps in reducing postoperative meningitis, surgical site, and extraneurosurgical site infections in neurosurgical patients, and prophylaxis with first-generation cephalosporin and aminoglycoside is effective.
Keywords: antibiotic prophylaxis; meningitis; wound infection